The Application of ScratchJr as an Interactive Learning Media to Improve Early Childhood Creativity - Hapsari, Carla Raysatama; Asmawulan, Tri (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to explore the application of the ScratchJr coding application as an interactive learning medium to develop creativity in early childhood. The focus is on how digital tools can support creative expression and cognitive growth in young learners. Methodology: The research employed a descriptive qualitative approach. Data were collected through observation of learning activities at KB Aisyiyah Smart Kids, interviews with the principal and classroom teacher, and documentation analysis, including samples of student work, activity documentation, and assessment sheets. Results: The study found that the ScratchJr application can be effectively used as an alternative interactive learning medium to enhance creativity in early childhood. The use of simple games and interactive storytelling within ScratchJr encouraged active engagement, improved cognitive and problem-solving skills, and supported creative expression among children. Applications/Originality/Value: This research highlights the educational value of integrating digital-based tools such as ScratchJr into early childhood learning. It provides practical insights into how interactive media can be leveraged to foster creativity, digital literacy, and holistic development in young learners.